2000
DOI: 10.1046/j.1365-2141.2000.02303.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of fluorescence in situ hybridization in mantle‐cell lymphoma

Abstract: Summary. Mantle-cell lymphoma (MCL) has a poorer prognosis than other small B-cell lymphomas, thus a definitive diagnosis is essential. The t(11;14)(q13;q32) associated with MCL juxtaposes portions of CCND1 (11q13) and IGH (14q32), resulting in over-expression of cyclin D1. In this study, a highly sensitive two-colour fluorescence in situ hybridization (FISH) method was developed to detect t(11;14)(q13;q32) in nuclei isolated from paraffin-embedded tissue. Twenty-three MCLs, 13 normal controls and nine small B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
92
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 42 publications
2
92
1
Order By: Relevance
“…Our percentage of detection appears higher than that in other series; for example Ott cyclin D1 immunoreactivity in 88% of cases with proven t(11;14)(q13;q32), whereas Aguilera et al (16) found immunoreactivity in 70% of 23 cases with proven translocation. According to cytogenetic and Southern blotting analyses, approximately 50 to 80% of MCL show the t(11;14)(q13;q32) translocation (16 -18), and, according to fluorescence in situ hybridization, up to 96% show it (19,20). Thus, despite the small number of cases analyzed and the likelihood that in studying a substantive number of cases, the positivity rate may fall, it appears that our conditions for the immunohistochemical detection of cyclin D1 were highly sensitive, particularly in BMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our percentage of detection appears higher than that in other series; for example Ott cyclin D1 immunoreactivity in 88% of cases with proven t(11;14)(q13;q32), whereas Aguilera et al (16) found immunoreactivity in 70% of 23 cases with proven translocation. According to cytogenetic and Southern blotting analyses, approximately 50 to 80% of MCL show the t(11;14)(q13;q32) translocation (16 -18), and, according to fluorescence in situ hybridization, up to 96% show it (19,20). Thus, despite the small number of cases analyzed and the likelihood that in studying a substantive number of cases, the positivity rate may fall, it appears that our conditions for the immunohistochemical detection of cyclin D1 were highly sensitive, particularly in BMs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that 6/10 cases of MCL had less than 25% of marrow involvement, that the neoplastic cells were cyclin D1 ϩ , and that none of the lymphocytes in reactive marrows showed cyclin D1 staining, in agreement with results from other studies (23,24). More recently, other approaches have been attempted to detect BM involvement; Remstein et al (19) and Caraway et al (25), in abstract forms, showed that fluorescence in situ hybridization is highly sensitive for detection of BM involvement by MCL, up to 96%; Caraway et al (25) showed that fluorescence in situ hybridization can detect t(11;14) breakpoints when polymerase chain reaction is negative.…”
Section: Discussionmentioning
confidence: 99%
“…Karyotype analysis allowed identification of t(11;14)(q13;q32) in only 70 to 75% of MCL, which may be related to the low mitotic index of malignant cells and to the poor morphology of metaphase spreads (9,27). Interphase fluorescence in situ hybridization (FISH) analysis circumvents these difficulties and has allowed the detection of t (11;14) in nearly 100% of MCL cases (8,28,29). Moreover, detection of t (11;14) by interphase FISH was achieved on cell suspensions or on nuclei isolated from fresh-frozen or paraffin-embedded material (8,29).…”
mentioning
confidence: 99%
“…Interphase fluorescence in situ hybridization (FISH) analysis circumvents these difficulties and has allowed the detection of t (11;14) in nearly 100% of MCL cases (8,28,29). Moreover, detection of t (11;14) by interphase FISH was achieved on cell suspensions or on nuclei isolated from fresh-frozen or paraffin-embedded material (8,29). Competitive or semi-quantitative reverse transcriptase polymerase chain reaction (RT-PCR) allowed to detection of cyclin D1 transcript overexpression in nearly all MCL cases (7,16).…”
mentioning
confidence: 99%
“…More recently, fluorescence in situ hybridization methods have become popular because large probes can be used to detect the widely scattered breakpoints on chromosome 11. Using these methods, the t (11;14) can be detected in Ͼ95% of MCL cases (13)(14)(15).…”
mentioning
confidence: 99%